„Ein Bild sagt mehr als Tausend Worte” – auch beim Vokabellernen? - Stork, Antie (Glottodidactica, 2006)
The vocabulary learning strategy „Image word’s meaning“ is often recommended in applied linguistics. The aim of the article is to find out if this supposition is true. Therefore, the underlying theories (levels of processes by Craik/Lockhart 1972 and the theory of dual coding by Paivio 1971/1985) are scrutinized. An empirical study of the author (Stork 2003) examines four vocabulary learning strategies with participants learning four sets of 20 word pairs: “Verbal repetition”, “Image word’s meaning”, “Keyword method”, “Use physical action when learning a word”. Tests were conducted (a) immediately after the sessions, (b) one week later, (c) two weeks later. The experiment demonstrates that the visualisation of foreign words is not better than rote rehearsal and that the proverb “A picture says more than a thousand words” is not true for the learning of foreign words. Consequences for the research and the teaching of vocabulary learning strategies are shown.